Healthy Learning Mind (HLM): Cluster Randomized Controlled Trial on A Mindfulness Intervention, Moderators and Association with Perceived Socioeconomic Status, and Comparison to Other National Data - Lassander Maarit; Saarinen Tapio; Simonsen-Rehn Nina; Suominen Sakari; Vahlberg Tero; Volanen Salla-Maarit (SPRINGER, 2022)
Background
This paper presents the baseline characteristics and their moderators in the Healthy Learning Mind (HLM)- school-based cluster-randomized controlled trial.
Objectives
The paper evaluates the state of various measures of well-being, their moderators and how these results compare to national and global norms/population studies.
Methods
Data were collected from all participants prior to the intervention and further analyzed by gender, grade and perceived socioeconomic status, including standardized measures for resilience, depressive symptoms and socioemotional functioning; health-related quality of life, dispositional mindfulness, satisfaction with life, compassion/self-kindness, self-rated health and morning tiredness.
Results
Participating 2793 students (1425 girls, 1368 boys), ages 12 to 15 years, filled in the questionnaires. The outcomes were in line with previous research, demonstrating gender differentiation and lower wellbeing among older children and adolescents.
Conclusions
All outcomes were associated with perceived socioeconomic status, suggesting that perceived low socioeconomic status should be addressed as a serious risk factor and included as a moderator in similar trials.